The official guide to Mermaid.js : create complex diagrams and beautiful flowcharts easily using text and code - Sveidqvist, Knut; Jain, Ashish (Packt Publishing, 2021)
Get up to speed with using Mermaid diagrams to facilitate a seamless development workflow with the help of real-world examples and expert tips from the creators of the tool Key Features Learn how to use and customize the different diagram types in Mermaid Discover examples of how to add Mermaid to a documentation system Use Mermaid with various tools available such as editors, wiki, and more Book Description Mermaid is a JavaScript-based charting and diagramming tool that lets you represent diagrams using text and code, which simplifies the maintenance of complex diagrams. This is a great option for developers as they're more familiar with code, rather than using special tools for generating diagrams. Besides, diagrams in code simplify maintenance and ensure that the code is supported by version control systems. In some cases, Mermaid makes refactoring support for name changes possible while also enabling team collaboration for review distribution and updates. Developers working with any system will be able to put their knowledge to work with this practical guide to using Mermaid for documentation. The book is also a great reference for looking up the syntax for specific diagrams when authoring diagrams. You'll start by learning the importance of accurate and visual documentation. Next, the book introduces Mermaid and establishes how to use it to create effective documentation. By using different tools, editors, or a custom documentation platform, you'll also understand how to use Mermaid syntax for various diagrams. Later chapters cover advanced configuration settings and theme options to manipulate your diagram as per your needs. By the end of this book, you'll be well-versed with Mermaid diagrams and how they can be used in your workflows. What you will learn Understand good and bad documentation, and the art of effective documentation Become well-versed with maintaining complex diagrams with ease Discover how to draw different types of Mermaid diagrams such as flowcharts, class diagrams, Gantt charts, and more Implement Mermaid diagrams in your workflows Understand how to set up themes for a Mermaid diagram or an entire site Get to grips with setting up a custom documentation system Who this book is for This book is for content generators such as technical writers, developers, architects, business analysts, and managers who want to learn effective documentation or how to effectively represent diagrams using simple text code snippets and ex ...